Blister fluid immunofluorescence in a case of pemphigus vulgaris - Shanmugasekar C; Ram Ganesh V; Jayaraman Alamelu; Srinivas C (Wolters Kluwer Medknow Publications, 2010)
Indirect immunofluorescence with serum is used in the diagnosis of pemphigus. We report a case in whom blister fluid was used as the specimen for indirect immunofluorecscence.